AN ANALYSIS OF MOOD AND SPEECH FUNCTION IN THE TONIGHT SHOW STARRING JIMMY FALLON TALK SHOW - nafalia, vina; Hartati, Elysa (Ma Chung Press, 2023)
This study aimed to find out the Interpersonal meaning that appeared in a conversation through the analysis of the Mood and speech function employed by the host and the guest star in The Tonight Show Starring Jimmy Fallon talk show. In analyzing the data, descriptive qualitative was used to interpret the data. The research findings showed that from the analysis, all of the Mood types were found in the conversation. The frequency of occurrence of types of Moods was 308 declarative, 11 interrogatives, and 5 imperatives. Meanwhile, there were only 3 speech functions out of 4 types of speech functions along with the responses employed by the host and the guest star. The data showed that the conversation was dominated by statements, followed by questions, and the last was command. Besides, both participants mostly responded to the interlocutor's statements by giving acknowledgment or contradiction. Both the host and the guest star were actively taking turns to initiate giving – a demanding exchange by adopting a speech role and assigning a complementary one to the other. It showed that understanding interpersonal communication was not enough by only analyzing the lexicogrammar of the Mood and speech function through the constructed clauses in any discourse, but more in how the language was able to make meaning and maintain a relationship